Determinants of Strategy Implementation in Agricultural Development Corporation - Bundotich, Samuel Kipngetich Kiptarus; Nzulwa, Dr. Joyce; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Current research indicates that the success rate in implementing strategies byorganizations stands between 10% and 30%. While strategy formulation is paramountand widely researched, little research has been done on strategy implementation hencethe need to carry out more research work in this area in order to build more knowledge.This study, therefore, concentrated on determinants of strategy implementation in theAgricultural Development Corporation (ADC). A descriptive research design was used inthe study, with a population of 340 employees of ADC. These comprised of 14 seniormanagers, 90 middle level managers and 236 low level employees. Stratified samplingwas conducted and a 20% sample resulting to 68 respondents was drawn. The study useda questionnaire with closed and open-ended questions to collect primary data. Secondarydata were collected from the ADC strategic plan: 2015-2019, consolidated annualreports & financial statements: 2012-15, strategic plan review report of 2013 andprogress reports which describe strategy implementation process in the corporation. Theresearcher checked the completed questionnaires for completeness and consistency ofinformation. The quantitative data were coded and analyzed using SPSS (statisticsPackage for Social Sciences) and presented using tables, charts, and graphs withrespective interpretation. Qualitative data were grouped into common themes based onthe research variables. The research found that strategic communication supportedstrategy implementation at the Agricultural Development Corporation. The evaluation ofeffect of strategic capability in the corporation established that the variable supportedstrategy implementation in the corporation. Similarly the study found that strategicflexibility supported strategy implementation at Agricultural Development Corporation.The study found a strong positive relationship between strategy implementation andcommunication process and organizational capability. A weak positive relationship wasestablished between strategy implementation and strategic flexibility. The study therefore,recommended that other state corporations implementing their strategic plans need togive attention to strategic communication, organizational capability and strategicflexibility.